Digital entrepreneurial ecosystem and female entrepreneurial activity - Yangjie Huang; Jiali Zhang; Ying Xu; Yue Yuan; Mengting Zhang; Leilei Huang (Humanities & Social Sciences Communications)
Abstract This study explores the relationship between the digital entrepreneurial ecosystem and female entrepreneurial activity in 45 countries using Fuzzy Set Qualitative Comparative Analysis (fsQCA). It highlights the importance of female entrepreneurship for economic and social development and examines how Digital Entrepreneurial Ecosystem elements collectively impact female entrepreneurial activity. Methodologically, it combines Necessary Condition Analysis (NCA) and fsQCA, using data from the Global Entrepreneurship Monitor (GEM) 2022 and the 2018 Global Digital Economy Development Index Report. The research identifies key Digital Entrepreneurial Ecosystem configurations that foster high levels of female entrepreneurial activity, characterized by varying societal norms and support systems. This approach challenges traditional linear models by highlighting a spectrum of conditions influencing female entrepreneurial activity. The study integrates Digital Entrepreneurial Ecosystem into female entrepreneurship analysis, providing insights for policymakers and stakeholders. This research contributes to a deeper understanding of how digital transformation influences the landscape of female entrepreneurship, emphasizing the role of digital ecosystems in promoting inclusive entrepreneurship.